Controversial questions of transport policy - Drahotský, Ivo (Univerzita Pardubice, 2010)
The report deals with the current situation in the sphere of transportation and the connection between transportation and the economic sector. There is an array of problems related to transportation, many of them, however, come more under the political sphere. On one hand we are forced to solve traffic jams, the ecological aspects of transportation, etc., on the other hand these activities usually mean additional costs for the users. Transportation also generates substantial funds for public finance which would fall should transportation be limited. There is of course the effort to balance the potential fall by funds that are obtained in other ways. Therefore, the question is whether the accountable authorities will be able to inform the users that they will pay more but get less.
Keywords: transport; transport policy; payment; transport infrastructure; financing; CO2; electronic tool